Differential Requirement for Phospholipase D/Spo14 and Its Novel Interactor Sma1 for Regulation of Exocytotic Vesicle Fusion in Yeast Meiosis - Riedel, Christian; Maier, Peter; Körner, Roman; Knop, Michael (The journal of biological chemistry, 2005)
During sporulation and meiosis of budding yeast a developmental program determines the formation of the new plasma membranes of the spores. This process of prospore membrane (PSM) formation leads to the formation of meiotic daughter cells, the spores, within the lumen of the mother cell. It is initiated at the spindle pole bodies during meiosis II. Spore formation, but not meiotic cell cycle progression, requires the function of phospholipase D (PLD/Spo14). Here we show that PLD/Spo14 forms a complex with Sma1, a meiotically expressed protein essential for spore formation. Detailed analysis revealed that both proteins are required for early steps of prospore membrane assembly but with distinct defects in the respective mutants. In the Δspo14 mutant the initiation of PSM formation is blocked and aggregated vesicles of homogenous size are detected at the spindle pole bodies. In contrast, initiation of PSM formation does occur in the Δsma1 mutant, but the enlargement of the membrane is impaired. During PSM growth both Spo14 and Sma1 localize to the membrane, and localization of Spo14 is independent of Sma1. Biochemical analysis revealed that Sma1 is not necessary for PLD activity per se and that PLD present in a complex with Sma1 is highly active. Together, our results suggest that yeast PLD is involved in two distinct but essential steps during the regulated vesicle fusion necessary for the assembly of the membranous encapsulations of the spores.